Transition from selexipag to oral treprostinil in a patient with pulmonary arterial hypertension. (1st March 2020) - Oriaku, Ifeoma; Patel, Amol; Safdar, Zeenat
Abstract : Prostacyclins are the mainstay treatment for patients with severe pulmonary arterial hypertension. This case highlights the transition from selexipag to oral treprostinil. Our patient improved both subjectively and objectively. Cardiac output and index, as measured by the echocardiogram, improved 12% and 7.7%, respectively. Invasive hemodynamic data revealed greater improvements: cardiac output improved by 25% and cardiac index by 28%. Mixed venous oxygen saturation improved from 65% to 71%. A possible explanation is that selexipag has a maximal dose, whereas there is no recommended maximum dose of oral treprostinil. Another theory is oral treprostinil has higher affinity to the IP receptor, though selexipag has a higher specificity. However, there are no bio‐equivalency data, and data comparing pharmacodynamics of both drugs are lacking. Furthermore, no head‐to‐head trials comparing these agents exist.